Engaging non-majors in MATLAB programming through a flipped classroom approach. Issue 4 (2nd October 2019) - McCord, Rachel; Jeldes, Isaac
ABSTRACT: Background and Context : Flipped classrooms are becoming more widely adopted across engineering higher education contexts. In degree programs where enrollment is increasing and undergraduate curricula are packed with content, pedagogies that allow more time for actively participate in classroom activities are being highly sought after to aid in increases in retention and persistence. Objective : The following study analyzed the impact of a flipped classroom intervention in a numerical analysis course teaching MATLAB programming taught to students not majoring in a computer-related engineering discipline. Method : Performance in the flipped classroom was compared to historical performance in the traditional classroom. Participants' intrinsic motivation was also investigated to try to understand the difference seen between semester offerings of the course. Findings : Student performance improved among students participating in the flipped classroom approach. Intrinsic motivation did not impact performance in the flipped classroom. Implications : Our work provides further evidence of the efficacy of flipped classroom approaches for teaching introductory programming. This work also highlights the importance of considering incoming knowledge and maturity when selecting flipped classrooms for educational contexts.